PEMBIASAAN SHOLAT DHUHA DALAM MENINGKATKAN KEDISIPLINAN MENUJU GENERASI EMAS 2045 SISWA MI ISLAMIYAH ATTANWIR TALUN SUMBERREJO BOJONEGORO - Robiatul Adawiyah; Nafi`Atus Tsaniyah; Dwi Frashinta; Siti Fadhilatum Mardhiyah (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to analyze the role of Dhuha Prayer habituation in enhancing students' discipline as part of the preparation for the Golden Generation 2045 at MI Islamiyah Attanwir Talun. This research is motivated by the importance of fostering discipline from an early age, particularly in Islamic educational environments that emphasize a balance between academic and spiritual aspects. Discipline is a crucial factor in educational success, and one approach to instilling it is through the habituation of religious practices, such as the Dhuha Prayer. This study employs a qualitative descriptive method, utilizing data collection techniques including observation, interviews, and documentation. The research subjects consist of students and teachers involved in the Dhuha Prayer habituation program at the madrasah. The findings indicate that the habituation of Dhuha Prayer contributes to improving time management, self-control, and adherence to school regulations. Furthermore, this program fosters respect, enhances spiritual motivation, and positively impacts students' discipline in both academic and social aspects. However, several challenges were identified in its implementation, such as maintaining students' consistency in performing the Dhuha Prayer and the role of teachers in providing continuous motivation.Thus, the habituation of Dhuha Prayer at MI Islamiyah Attanwir Talun has proven to be an effective strategy in shaping students' discipline and can serve as a valuable approach to character education in madrasahs.